Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1155/2021/5571793
|View full text |Cite
|
Sign up to set email alerts
|

Use of Narrow-Diameter Implants in Completely Edentulous Patients as a Prosthetic Option: A Systematic Review of the Literature

Abstract: Objective. The objective of the present review is to assess the implant survival, marginal bone loss, and biomechanical features of narrow-diameter implants (2.5-3.5 mm) supporting or retaining full-arch fixed or removable restorations. Materials and Methods. Three operators screened the literature (PubMed, Cochrane Library, and Google Scholar) and performed a hand search on the main journals that focus on implantology until 24 March 2019. Only articles that considered full-arch restorations supported or retai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“… 22 No cases of fixed rehabilitation on these devices have been reported in the literature until now. 5 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 22 No cases of fixed rehabilitation on these devices have been reported in the literature until now. 5 …”
Section: Discussionmentioning
confidence: 99%
“…The most frequently described indications were the edentulous arch and single arch non‐load‐bearing teeth in the anterior region. 4 , 5 The reported mean survival rate was 94.7 ± 5% (range: 80%–100%) with a mean follow‐up of 34 ± 20 months (range: 12-78 months). 4 Only one study indicated an implant success rate of 92.9% with a mean marginal bone loss ranging from 0.6 to 1.43 mm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Por el contrario, los pacientes tratados en condiciones de control generalmente son rehabilitados con tratamientos y procedimientos básicos sin refuerzo de estructuras o derivaciones prolongadas. (18) Tabla 1. Resumen de documentos incluidos para revisión (2019) (9) España Artículo de revisión Utilización de dentina autógena como material de injerto en cirugías bucal Conocer el estado actual del empleo de dentina como injerto autógeno en diferentes procedimientos en cirugía bucal.…”
Section: éXito De Los Procedimientosunclassified
“…Bien indicado y planificado, permite la fabricación de más prótesis estables evitando molestias y lesiones. Es un tema importante, con cierta escasez de datos en la literatura, siendo necesario más estudios publicados 11 Storelli S, Caputo A, Palandrani G, Peditto M, Del Fabbro M, Romeo E & Oteri G. (2021) (18) Italia Artículo de revisión Use of narrow-diameter implants in completely edentulous patients as a prosthetic option: a systematic review of the literature Evaluar la supervivencia del implante, la pérdida ósea marginal y las características bio-mecánicas de implantes de diámetro estrecho que soportan o retienen restauraciones fijas o removibles de arcada completa Con las limitaciones del presente estudio, hay pruebas que los implantes de 2,5-3,5 mm de diámetro estrecho retienen una restauración removible, pudiendo ser un tratamiento exitoso en pacientes totalmente desdentados. No se disponía de datos sobre restauraciones fijas.…”
Section: Restablecimiento Oclusal Mediante Procedimientos Multidiscip...unclassified